Erratum to “Technical note: Accuracy checks of physical beam modifier factors algorithm used in computerized treatment planning system for a 15 MV photon beam” [Rep. Pract. Oncol. Radiother. 14 (2009) 214–220] - Muhammad, Wazir; Maqbool, Muhammad; Shahid, Muhammad; Ahmad, Misbah; Matiullah, Matiullah (Reports of practical oncology and radiotherapy, 2010)
[This corrects the article DOI: 10.1016/j.rpor.2009.12.002.].